The study on Work Load Calibration by using Step Test and Ergometer test was carried out in order to find the best way 10 calibrate the data measurement and to predict human work load by using heart rate data. This study was conducted on four male subjects. but the data analysis has just been done to three subjects due one of the subject was insufficient performance. The sport tester PE3000 heart rate monitor is used for measuring the heart rate data which will be useful for predicting the work - Roni Kastaman; Sam Herodian (Jurnal Keteknikan Pertanian, 1998)
The study on Work Load Calibration by using Step Test and Ergometer test was carried out in order to find the best way 10 calibrate the data measurement and to predict human work load by using heart rate data. This study was conducted on four male subjects. but the data analysis has just been done to three subjects due one of the subject was insufficient performance. The sport tester PE3000 heart rate monitor is used for measuring the heart rate data which will be useful for predicting the work load on each activity. The linear regression method is also used to predict the work load based on the heart rate data, so that the best alternative scenario data input will be able to determined by comparing the correlation coefficient or coefficient of determination.